Effects of collagen-calcium alginate composite film with therapeutic ultrasound massage on open wound in rats and cats - Hussin, Khaled M. A. (2014)
This study was conducted with the hypothesis that collagen-calcium alginate film and therapeutic ultrasound massage are effective wound healing stimulants causing early re-epithelialization and uncomplicated wound healing. The objective of this study was to identify and evaluate wound healing properties of collagen-calcium alginate film and therapeutic ultrasound massage on open wounds in rats. One hundred and twenty healthy Sprague-Dawley rats were used in the study. Ketamine (5 mg/kg) and Xylazine (50 mg/kg) combination was used. A skin wound (2x2cm) was created lateral to the spine between the base of the scapulae and the iliac crest.The rats were randomly divided into four groups (n = 30) namely Group I (control group), Group II (treated with therapeutic ultrasound massage), Group III (treated with collagen-calcium alginate film) and Group IV (treated with collagen-calcium alginate film with therapeutic ultrasound massage). Evaluation on the effect of biomaterials on open wound was based on clinical observation, haematological,bacteriological, biochemical and histopathological examinations on day 4, 8, 12, 16 and 20 (post-wounding). The collagen-calcium alginate films with therapeutic ultrasound massage were well accepted and tolerated by animals and did not cause any adverse reactions. Animals in Group IV showed bright red granulation tissue, without malodour and exudates on day 20 post-wounding. This group also had a higher mean percentage of wound epithelialization, wound contraction, and total wound healing was significantly higher (P<0.05) compared to the other group. Staphylococcus aureus, Klebsiella spp., Proteus spp. and Pseudomonas spp. were isolated from all animals. Wound of surgical or traumatic origin is invariably colonized by bacteria. Among the common micro-organisms associated with wound infection are Staphylococcus aureus and beta-haemolytic Streptococcus which are considered as transient flora of the skin. Day 8 post-wounding, typical histological appearance of mature fibroblasts with relatively loose type of supporting tissue was noticed. The fibroblast nuclei were elongated in the direction of the collagen fibers with neovacularization in animals in group IV. The predominant nucleoli reflect active protein synthesis in wound healing. Clinically Collagen-calcium alginate film with therapeutic ultrasound massage was effective when used in rats, it is used in clinical cases involving 8 cats presented at rogressive Animal Welfare society (PAWS).. All the cats. No animals showed any intolerance and disturb did not the bandage throughout the treatment. Formation of healthy granulation tissue was observed in all the cases without any side effects. As a conclusion, collagen-calcium alginate film with therapeutic ultrasound massage was an effective wound healing stimulant. This biomaterial combination also was found to be better than Collagen-calcium alginate film or therapeutic ultrasound massage alone. The findings have a commercial application because it is inexpensive alternative to stimulate wound healing in animals where the cost of treatment is a major concern.